2019
DOI: 10.3233/jad-180573
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with the High Prevalence of Dementia in Older Aboriginal Australians

Abstract: Dementia prevalence in Aboriginal and Torres Strait Islander Australians is three to five times higher than the general Australian population. A better understanding of the underlying biomedical and social risk factors is needed to guide dementia prevention in Aboriginal Australians. The current study is the first to examine potential risk factors for dementia in the majority urban and regional population, with a representative sample of 336 Aboriginal Australians aged 60 years and older. Participants included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
74
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(78 citation statements)
references
References 38 publications
3
74
1
Order By: Relevance
“…Radford et al's study [19] of factors associated with dementia in a sample of 336 Aboriginal Australians aged 60+ years illustrates both the promise and challenges of focusing research attention in communities rarely represented in dementia studies. Previous work indicates Aboriginal Australians have substantially higher dementia risk than other Australians [20], and although the existing evidence base is limited, this demonstrates the relevance of ADRD for Aboriginal health.…”
Section: S7mentioning
confidence: 99%
See 2 more Smart Citations
“…Radford et al's study [19] of factors associated with dementia in a sample of 336 Aboriginal Australians aged 60+ years illustrates both the promise and challenges of focusing research attention in communities rarely represented in dementia studies. Previous work indicates Aboriginal Australians have substantially higher dementia risk than other Australians [20], and although the existing evidence base is limited, this demonstrates the relevance of ADRD for Aboriginal health.…”
Section: S7mentioning
confidence: 99%
“…Previous work indicates Aboriginal Australians have substantially higher dementia risk than other Australians [20], and although the existing evidence base is limited, this demonstrates the relevance of ADRD for Aboriginal health. Radford et al [19] identified social (childhood trauma and low-skill occupation), behavioral (past high-risk alcohol use) and medical conditions (stroke, head injury) as significant predictors of prevalent dementia. These results are not surprising and indicate general consistency with dementia predictors in other studies, although Radford et al [19] note that education in this sample was not independently associated with dementia.…”
Section: S7mentioning
confidence: 99%
See 1 more Smart Citation
“…There is increasing evidence that prevention and management of vascular and other risk factors could delay progression of dementia [9], and this may be of particular relevance in Aboriginal and Torres Strait Islander communities where there are high rates of co-morbid conditions [10,11] and onset at earlier ages, including past head injurya key risk factor associated with decline from normal cognition to impairment [4], and other associations including age, stroke, non-aspirin analgesics, lower BMI, and higher systolic blood pressure (BP) [4]. In addition childhood trauma was found to be a contributor to cognitive decline in urban regions [6,12].…”
Section: Introductionmentioning
confidence: 99%
“…In a comprehensive umbrella review of systematic reviews, Anstey and colleagues summate the observational evidence on risk factors for Alzheimer's disease, vascular dementia, and any dementia, and highlight the lack of evidence for many risk factor exposures in midlife, a lack of data on risk factors for vascular dementia and from low and middle income countries [15]. The editorial from Glymour and Whitmer takes this further highlighting the need for a life-course understanding, and the importance of risk factor prevalence or saturation in particular populations or those with relatively small numbers (for example indigenous Australian populations) [14,16]. Glymour and Whitmer also helpfully suggest new ways in which we can start to conceptualize, examine, and combine our data to gain the greater understanding we need for future risk reduction [14].…”
mentioning
confidence: 99%